Answer:
-5x^2+125
Explanation:
You need to go step-by-step here. I would actually prefer to multiply by 5 at the end, because it's easier that way. (You can multiply the terms in any order you want, though.)
So first, multiply (5-x)(5+x). This is a special product: (a-b)(a+b)=a^2-b^2, so:
(5-x)(5+x)=5^2-x^2=25-x^2
But even if you don't know that special product, you can multiply it out. Rewrite (5-x)(5+x) as 5(5+x)-x(5+x).
5(5+x)-x(5+x)
=25+5x-(5x+x^2)
=25+5x-5x-x^2
=25+0x-x^2
=25-x^2
As you can see, the result is the same regardless of you get it. Now multiply that by 5 to get 125-5x^2, or in standard form, -5x^2+125.
Hope I could help you!